A presentation of E-Cigarette vaping associated lung injury (EVALI) caused by THC-Containing electronic smoking device. (2020) - Galo, Jason; Celli, Diego; Gross, Dana; Holt, Gregory; Campos, Michael
Abstract: Several cases have recently been reported concerning the development of a syndrome of acute lung injury associated with the use of electronic cigarettes, leading to respiratory failure and several deaths. We present a case of a young veteran who presented with e-cigarette vaping associated lung injury (EVALI) to a primary care clinic and who required subsequent inpatient admission and home oxygen therapy after discharge. The patient afterwards improved after a three-month course of steroids and cessation of THC-containing electronic cigarettes, consistent with previously reported cases. Furthermore, evidence on bronchoscopy and biopsy demonstrated intracellular lipid droplets in the patient's macrophages. This outpatient case of EVALI prompts primary care providers to raise suspicion of this condition, and enquire about the use of e-cigarettes, particularly THC-containing vaping products. Furthermore, in the setting of the COVID-19 pandemic, similar clinical and radiographic presentations between COVID-19 and EVALI can be seen.